A NEW SPECIES OF FERULA (UMBELLIFERAE) FROM SOUTHERN IRAN - Ajani, Y.; Ajani, M. (Edinburgh Journal of Botany, 2008)
A new species of Ferula (Umbelliferae), Ferula hezarlalehzarica Y.Ajani, from the Hezar and Lalehzar mountains (Kerman province) in the south of Iran, is described and illustrated. From field and herbarium studies it appears that the species is found only in Kerman province. Details of its morphology and mericarp anatomy are discussed and compared with its closest relatives, Ferula hindukushensis Kitam. and F. koso-poljanskyi Korovin. The new species differs from these mainly in leaf, umbel and mericarp characters. An alteration to the Ferula key in Flora Iranica is given.
Keywords: Ferula; fruit anatomy; Iran; new species; Umbelliferae/Apiaceae